Anticardiolipin antibodies in patients from Malaysia with systemic lupus erythematosus. Issue 3 (March 1991) - Jones, H W; Ireland, R; Senaldi, G; Wang, F; Khamashta, M; Bellingham, A J; Veerapan, K; Hughes, G R; Vergani, D
Abstract : Systemic lupus erythematosus (SLE) is highly prevalent in Malaysia, which has a mixed population of Malays, Chinese, and Indians. A quantitative enzyme linked immunosorbent assay (ELISA) was used to determine anticardiolipin antibody (aCL) levels (total immunoglobulin, IgG, and IgM) in 200 patients with SLE (164 Chinese, 26 Malay, and 10 Indian) attending the University Hospital of Kuala Lumpur, Malaysia, and 103 matched controls. Only 33 (16.5%) of the patients had raised aCL levels; 26 had raised IgG aCL, five IgM aCL, and two both IgG and IgM aCL. There was a low prevalence of raised levels of aCL in the population studied, which was seen in conjunction with a rare occurrence of thrombosis. The classical association of high aCL levels with thrombocytopenia and recurrent abortions was noted, though not with cerebral disease. The low prevalence of aCL in this study population of mixed racial origin contrasts with findings in European patients with SLE and lends support to the influence of local factors, be they genetic or environmental, on the clinical manifestations of this disease.